The Impact Of The Annual Flood Disaster On The Socio-economic Conditions Of The Community In Nagari Taram, Harau Sub-district, Fifty–city District - Ninda Mulyani; Ernawati Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This study aims to determine: (1) The impact of the annual flood disaster on the social conditions of the people in Nagari Taram, Harau District, Fifty City District. (2) The impact of the annual flood disaster on the economic conditions of the community in Nagari Taram, Harau District, Fifty Cities District. (3) Mitigation and adaptation to annual flood disasters. This research is a descriptive quantitative type. Sampling is purposive sampling. The population is 189 households. The sample is 112 households. Data collection tools with observation, interviews, questionnaires / questionnaires. Data analysis techniques by scoring the impact of floods, assessing the impact of floods, classifying the effects of floods and paired t-test. The results of the study show that (1) The impact of the annual flood disaster on the social conditions of the community is very high with a qualification of 94.12% in terms of demographic conditions, health, education and housing conditions. (2) The impact of the annual flood disaster on the community's economic conditions is very high with a qualification of 83.04% as seen from the livelihoods, income and ownership of goods. (3) Mitigation and adaptation to floods by normalizing rivers. As for flood disaster adaptation, the steps taken are raising the floor of the building and adding houses, implementing patterns and timing of planting on agricultural land, holding socialization on disaster management.